POST-TRANSPLANT LYMPHOPROLIFERATIVE DISORDER AFTER AUTOLOGOUS PERIPHERAL STEM CELL TRANSPLANTATION IN A ADULT PATIENT: CASE REPORT - FZ Piazera; JVP Neto; LHA Ramos; RS Vasconcelos (Hematology, Transfusion and Cell Therapy)
Introduction: Post-Transplant Lymphoproliferative Disorder (PTLD) is a complication of allogeneic Bone Marrow Transplantation (BMT). Rare cases of PTLD after autologous BMT have been reported only in adults. This case report described PTLD in a patient after autologous Peripheral Stem Cell Transplantation (PSCT), and this condition is rare in patients who do not have HIV and are late after transplantation. Materials: We report a case of EBV lymphoproliferative disease 2-years after autologous transplantation for Diffuse Large B-Cell Lymphoma germinal center subtype. Results: This 66-year-old male with stage IVB Lymphoma Diffuse Large Cell B underwent autologous PSCT post first relapse. On day 650 post PSCT, patient started with night sweats, afternoon fever, asthenia and increased abdominal volume. On physical examination, no lympfondomegaly was found, but a voluminous splenomegaly was identified with 10 cm below the left costal margin. Opportunistic infections research was conducted: negative CMV PCR, Leishmaniose negative, Chagas negative, IGRA para Tuberculose negative, Toxoplasmose Negativo, HIV, HTLV, Hepatite B e C negative, HHV6 negative. PCR polymerase was conducted on whole blood EBV DNA, and DNA levels increased up to 2.11×103 copies/mL. Laboratory studies have shown normal levels of IgG, IgA, IgM. The bone marrow biopsy immunohistochemical analysis showed that the lymphocytes were positive for CD20, according to the immunophenotype below: Flow cytometric immunophenotyping analysis of the specimen revealed that the proportion of surface: 86.58% of the B lymphocytes (1.66% of the total cells analyzed) expressed CD19, CD20 (strong), CD23 (weak), CD45 (strong), CD79b, CD81 and lambda light chain restriction, without expression of CD10, CD38, CD43, CD200, CD305 or other markers investigated. 0.12% were plasma cells without immunophenotypic alterations (ckappa/clambda: 1.47). The patient presented a probable clinical presentation of EBV lymphoproliferative disease after autologous transplantation-mononucleosis like, the patient was treated with weekly rituximab and monitoring of EBV levels, with complete negative viral load and complete remission of the condition after 4 doses of rituximab. Monthly PCR monitoring for EBV with an undetectable viral load was performed after 6-months of evolution. Conclusion: New approaches for diagnosis and monitoring based on quantitative polymerase chain reaction for EBV DNA are being explored. What exactly is being measured (the source and character of the viral DNA) has yet to be determined, as well as the compartment that should be analyzed (whole blood, serum, plasma, or lymphocytes). Despite these issues, there is an emerging consensus that these technologies will facilitate rapid diagnosis and therapeutic monitoring in the future. A myriad of therapeutic interventions are or will be available. Rituximab, alone or in addition to other therapies, promises a profound change in the landscape with respect to the treatment and perhaps prevention of post-transplant lymphoproliferative disease.